2008
DOI: 10.1096/fj.08-105726
|View full text |Cite
|
Sign up to set email alerts
|

Impaired skeletal muscle development and function in male, but not female, genomic androgen receptor knockout mice

Abstract: To identify mechanisms of anabolic androgen action in muscle, we generated male and female genomic androgen receptor (AR) knockout (ARKO) mice, and characterized muscle mass, contractile function, and gene expression. Muscle mass is decreased in ARKO males, but normal in ARKO females. The levator ani muscle, which fails to develop in normal females, is also absent in ARKO males. Force production is decreased from fast-twitch ARKO male muscle, and slow-twitch muscle has increased fatigue resistance. Microarray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
197
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(221 citation statements)
references
References 45 publications
(61 reference statements)
18
197
6
Order By: Relevance
“…3). This observation is in agreement with recent findings in ARKO mice where classic MRF genes were not regulated, and the overall gene profile suggested that androgens delay differentiation allowing clonal expansion of myoblasts (MacLean et al 2008). These data do not exclude the possibility that these genes are involved in androgenic anabolism, as they could be regulated in a small proportion of cells, by a post-transcriptional mechanism, or at later time points.…”
Section: Discussionsupporting
confidence: 88%
“…3). This observation is in agreement with recent findings in ARKO mice where classic MRF genes were not regulated, and the overall gene profile suggested that androgens delay differentiation allowing clonal expansion of myoblasts (MacLean et al 2008). These data do not exclude the possibility that these genes are involved in androgenic anabolism, as they could be regulated in a small proportion of cells, by a post-transcriptional mechanism, or at later time points.…”
Section: Discussionsupporting
confidence: 88%
“…Raldh1 , which encodes the RA synthetic enzyme retinaldehyde dehydrogenase 1 present in tanycytes (Shearer et al, 2010), was investigated as a gene regulated by several nuclear receptor family members (Fujiwara et al, 2009; Huq et al, 2006; MacLean et al, 2008). This gene was significantly upregulated in the hypothalamus of T3‐treated rats (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However despite considerable investigation, the genes directly regulated by TH in the hypothalamus are largely unknown; indeed, the genes regulated by TH in much of the brain remain undiscovered. Retinaldehyde dehydrogenase 1 (Raldh1, also known as Aldh1a1) is regulated by a number of hormone activators of nuclear receptors, such as estrogen (Fujiwara et al, 2009) and androgen (MacLean et al, 2008), as well as metabolite‐regulated nuclear receptors such as LXR (Huq et al, 2006). Via its synthesis of retinoic acid (RA) from retinaldehyde, Raldh1 itself then controls the activity of further nuclear receptors, the retinoic acid receptors (RARs).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that Global-ARKO mice have increased fat mass and decreased lean mass, resulting in an overall decrease in body weight. (21,38,42) Replacement of the AR in osteoblasts from either the proliferative or mineralization stage of their maturation in Global-ARKO mice further reduced their body weight such that body weight in the pOBL-and mOBL-AR gene replacement mice was lower compared with Global-ARKOs. This is in line with the reduced body weight we observed in the pOBLAR-tg and mOBLAR-tg mice after their backcrossing to a C57BL/6 background, before their use to generate the pOBL-and mOBL-AR gene replacement mice.…”
Section: Discussionmentioning
confidence: 99%